2014
DOI: 10.1016/j.apt.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent effect of gold nanospheres on the acoustic pressure pulses from laser-irradiated suspensions

Abstract: We carried out the experimental measurements of photoacoustic responses, where the suspensions of spherical gold nanoparticles (NPs) of different diameters (20, 40, and 50 nm) in water at different concentrations and different temperatures (4 and 20 °C) were irradiated by 0.8-ns laser pulses. In the case of 20 °C, the values of photoacoustic signals normalized by the light absorbance of the NP suspension decreased with increasing the NP size. The photoacoustic signals at 4 °C were significantly reduced compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In particular, the strong signal observed at T 0 = 4 • C for which β 0 = 0 is purely nonlinear in nature as the linear contribution vanishes at this temperature. This has first been observed experimentally by Hunter et al41 in protons experiments and has been more recently reported with gold nanoparticles by Fukasawa et al31 and Simandoux et al22 . Recent experimental measurements of the photoacoustic amplitudes as a function of equilibrium temperature with 40-nm diameter gold nanospheres by Simandoux et al22 are in good agreement with the predictions given inFig.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…In particular, the strong signal observed at T 0 = 4 • C for which β 0 = 0 is purely nonlinear in nature as the linear contribution vanishes at this temperature. This has first been observed experimentally by Hunter et al41 in protons experiments and has been more recently reported with gold nanoparticles by Fukasawa et al31 and Simandoux et al22 . Recent experimental measurements of the photoacoustic amplitudes as a function of equilibrium temperature with 40-nm diameter gold nanospheres by Simandoux et al22 are in good agreement with the predictions given inFig.…”
supporting
confidence: 66%
“…Other studies provided theoretical expressions for the photoacoustic emission by spherical absorbers, but with assumptions not always valid in this work and more importantly also limited to the linear regime 28,29 . Two recent studies also reported comparisons between experimental results and theoretical predictions in the linear regime 30,31 , but the authors assumed heat and stress confinement at the scale of a whole particle suspension and did therefore not consider the photoacoustic generation at the scale of individual particles.…”
mentioning
confidence: 99%
“…For fluences just above a certain threshold, the temperature of the NPs can exceed the boiling temperature of the surrounding host liquid. Thus, a vapor layer appears on the surface of the NP, which rapidly expands generating PA signals [10,26,[28][29][30][31]38]. In the case of NPs fabrication the ablation process originates the PA effect.…”
Section: Introductionmentioning
confidence: 97%
“…• Colloid parameters: nanoparticles material [30], nanoparticles concentration [29,31], nanoparticles size [10,29,31], colloid temperature [10,31,32] and the properties of the liquids [31,32]. • Other parameters: the cavitation bubble [33] and other microbubbles [28,34].…”
Section: Introductionmentioning
confidence: 99%
“…The photoacaustic imaging technique was employed for using biomedical science (Oraevsky, Jacques & Tittel, 1997;Kruger, 1994;Ku et al, 2005;Wang et al, 2002). Properties of silver nanoparticles can also be used in the wide range of different field of integrated circuits, biosensors, medical imaging, drug delivery, hyperthermia therapy, chemosensors, electrochemical sensors, bio labeling, and filters because of exhibiting an antibacterial activity as well as surface plasmon resonance (Pal, Tak, & Song, 2007;Abbasi et al, 2016;Amendola & Meneghetti, 2009;Fukasawa et al, 2014;Schröfel et al, 2014). In addition, many pure metals-based nanoparticles emerge unusual properties that have discussed optical, electrical, and magnetic properties (Chen et al, 2009;Garitaonandia et al, 2008;Hao & Schatz, 2004;Mock et al, 2002;Sun, & Xia, 2002).…”
Section: Introductionmentioning
confidence: 99%